Cyclic Group Action of Composite Order on Indefinite 4-Manifolds (Communications in Mathematical Research, 2021)
In this paper, we study the possibilities for several kinds of topological,locally linear cyclic group actions of non-prime order on some closed, simply connected4-manifolds with indefinite intersection form. Especially, we discuss the existence oflocally linear pseudofree $C_9$ action on this kind of 4-manifolds.